Managing the financial risks affecting construction contractors: implementing hedging in Sri Lanka - Fernando, Charith Kaushalya; Hosseini, M. Reza; Zavadskas, Edmundas Kazimieras; Perera, B. A. K. S.; Rameezdeen, Raufdeen (International Journal of Strategic Property Management, 2017)
The aim of this study is to ascertain the major financial risks affecting construction contractors in Sri Lanka and to investigate the suitability of available hedging techniques as remedial solutions in managing such financial risks. To this end, the study identifies the most serious financial risks and the most commonplace hedging techniques to deal with the identified risks for Sri Lankan contractors through three unstructured interviews and a questionnaire survey administered among financial experts resulting in 33 duly completed responses. Analysis of the results is performed mainly using Analytic Hierarchy Process (AHP) methodology. As per the findings, the most serious financial risk affecting contractors was found to be associated with variations in material prices. The most commonplace hedging technique used by contractors to deal with the identified financial risks was ‘forward contracts’. The study prioritises the hedging techniques with respect to their suitability for dealing with financial risks in form of an integrated model. This study provides an illuminating insight into financial risks and measures to mitigate them through implementing hedging techniques with a focus on construction contracting in Sri Lanka. The findings can be held up as examples for other developing countries suffering from similar issues.